Building better products with finite element analysis - Adams, Vince, 1963-; Askenazi, Abraham (Santa Fe, NM : OnWord Press, 1999)
This book is divided into four parts: Introduction to FEA and the analytical method; Finite element modeling basics; Advanced modeling techniques and applications; and Integrating simulation into product design strategy.
Keywords: Finite element method; Finite element method